KETERAMPILAN DASAR INTERAKSI SOSIAL SISWA KELAS OLIMPIADE SCIENCE MATHEMATHIC ENGLISH DI MIM PK KARTASURA - Arjun Dwi Fadlullah; Vivi Aryati Sapta Ningrum; Fitriana Nurrul Khotimah; Annisa Sholihah Irfani (Buletin Literasi Budaya Sekolah, 2022)
The purpose of this research to determine the basic social interaction skills possessed by 4th grade students of Olympiad or SME (Science Math English) MIM PK Kartasura. The research was conducted using a descriptive qualitative approach with direct observation and interviews with sources related to their fields. This research activity was carried out using three stages. The first stage is observing the daily activities of students, the second stage is conducting interviews with people in the environment around them, such as homeroom teachers and classmates, and the third stage is combining the data that has been found and concluding the results. The results of this study indicate that the basic skills of social interaction in the SME class at MIM PK are good. This can be realized because MIM PK Kartasura has professional teachers who can make students not easily bored and happy with the learning that is going on, and is supported by various programs implemented by the school.